Late Cenozoic tephrostratigraphy offshore the southern Central American Volcanic Arc: 2. Implications for magma production rates and subduction erosion. (21st November 2016) - Schindlbeck, J. C.; Kutterolf, S.; Freundt, A.; Straub, S. M.; Vannucchi, P.; Alvarado, G. E.
Abstract: Pacific drill sites offshore Central America provide the unique opportunity to study the evolution of large explosive volcanism and the geotectonic evolution of the continental margin back into the Neogene. The temporal distribution of tephra layers established by tephrochonostratigraphy in Part 1 indicates a nearly continuous highly explosive eruption record for the Costa Rican and the Nicaraguan volcanic arc within the last 8 Myr. The widely distributed marine tephra layers comprise the major fraction of the respective erupted tephra volumes and masses thus providing insights into regional and temporal variations of large‐magnitude explosive eruptions along the southern Central American Volcanic Arc (CAVA). We observe three pulses of enhanced explosive volcanism between 0 and 1 Ma at the Cordillera Central, between 1 and 2 Ma at the Guanacaste and at >3 Ma at the Western Nicaragua segments. Averaged over the long‐term the minimum erupted magma flux (per unit arc length) is ∼0.017 g/ms. Tephra ages, constrained by Ar‐Ar dating and by correlation with dated terrestrial tephras, yield time‐variable accumulation rates of the intercalated pelagic sediments with four prominent phases of peak sedimentation rates that relate to tectonic processes of subduction erosion. The peak rate at >2.3 Ma near Osa particularly relates to initial Cocos Ridge subduction which began at 2.91 ± 0.23 Ma as inferred by the 1.5 Myr delayed appearance of the OIB geochemical signal in tephras from Barva volcano at 1.42 Ma. Subsequent tectonic re‐arrangements probably involved crustal extension on the Guanacaste segment that favored the 2–1 Ma period of unusually massive rhyolite production. Key Points: Central American Volcanic Arc volcanism Magma Production rates Sedimentation rates offshore Costa Rica and Nicaragua